Hands on film actants, aesthetics, affects - Monahan, Barry 1973- (Amsterdam University Press, 2022)
Hands on Film is a comprehensive study of the representations and uses of that human limb from the birth of cinema to contemporary times. It examines how filmmakers have framed the hand for a variety of effects, from stylistic to thematic, and for the development of characterisation and narrative. The book offers insights into how films have created meaning by focusing on that part of the anatomy and, in turn, proposes a variety of ways in which its on-screen appearances might shed light on what it means to be sentient, cultured, and creative beings in the world
Title from publisher's bibliographic system (viewed on 16 Nov 2022)
Keywords: Human body in motion pictures